(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, large, medium and small companies face an accelerated development and multiple challenges that test their ability to overcome and permanence. For this reason, Companies which seet to remain in a consumer market must keep in constant change and continuous improvement of their processes, procedures and other internal and external factors that influence the development of products, services and designs. It is remarkable to see how many of these companies have decided to design and implement tools that allow them to maintain control of their processes for better results, which ultimately could translate into the optimization of the processes. This paper shows how algorithms such as ant colony, k-means and other statistical tools influence and improve the expected results, the research was supported by four phases of development, starting with a diagnosis of the processes to be analyzed and ending with the validation of the tools, whose results show an improvement in the processes.